2017
DOI: 10.1016/j.bjpt.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of resistance exercise compared to aerobic exercise without insulin therapy in patients with type 2 diabetes mellitus: a meta-analysis

Abstract: HighlightsResistance exercise (> 12 weeks) appears to increase in VO2max in diabetic patients.Resistance exercise didn’t decrease the glycemic level compared to aerobic exercises.The lipid profile of DM patients was the same in both types of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 38 publications
0
27
0
4
Order By: Relevance
“…Moderate-intensity (40–50%) high-volume resistance training had no effect on HbA1c levels in diabetic subjects [19]. Based on the duration of RE, a recent meta-analysis categorized seven trials into two subgroups, 8–20 weeks (four trials) and 21–48 weeks (three trials), and found no differences in HbA1c between the subgroups and also with overall RE [63]. None of these studies categorized RE based on its intensity, and compared intensity effects on change of HbA1c in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate-intensity (40–50%) high-volume resistance training had no effect on HbA1c levels in diabetic subjects [19]. Based on the duration of RE, a recent meta-analysis categorized seven trials into two subgroups, 8–20 weeks (four trials) and 21–48 weeks (three trials), and found no differences in HbA1c between the subgroups and also with overall RE [63]. None of these studies categorized RE based on its intensity, and compared intensity effects on change of HbA1c in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Weightlifting exercise is well established as an exercise modality of resistance exercise to improve skeletal muscle mass [ 1 , 2 ], strength [ 3 , 4 , 5 ], endurance [ 6 , 7 ] and power [ 8 , 9 ]. These positive adaptations in skeletal muscle function translate into athletic performance [ 10 , 11 , 12 , 13 , 14 ] and health-related [ 15 , 16 , 17 , 18 , 19 ] benefits in a range of populations [ 20 , 21 , 22 ]. To achieve specific muscular adaptations, resistance exercise training programs can manipulate variables such as muscle action, loading and volume, exercise selection and order, free weights vs. resistance machines, rest periods, number of repetitions and sets, velocity of muscle action and frequency [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…No total, o volume de tempo de exercícios físicos foi de (WEWEGE et al, 2018). Esse resultado vai de encontro com outra metanálise, publicada em 2017, que mostrou não haver diferença entre os níveis de HbA1c, índice de massa corporal (IMC), colesterol HDL e LDL, triglicerídeos após programas de treinamento resistido ou aeróbico, com duração maior que 8 semanas (NERY et al, 2017).…”
Section: Discussionunclassified